2018
DOI: 10.1126/scitranslmed.aar3342
|View full text |Cite
|
Sign up to set email alerts
|

MHC proteins confer differential sensitivity to CTLA-4 and PD-1 blockade in untreated metastatic melanoma

Abstract: Combination anti-cytotoxic T lymphocyte antigen 4 (CTLA-4) and anti-programmed cell death protein 1 (PD-1) therapy promotes antitumor immunity and provides superior benefit to patients with advanced-stage melanoma compared with either therapy alone. T cell immunity requires recognition of antigens in the context of major histocompatibility complex (MHC) class I and class II proteins by CD8 and CD4 T cells, respectively. We examined MHC class I and class II protein expression on tumor cells from previously untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
414
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 465 publications
(448 citation statements)
references
References 60 publications
26
414
0
8
Order By: Relevance
“…This is in line with recent observations that PD-L1 ( CD274 ) is a BCL6-supressed gene 41 , and a well-characterized role for PD-L1 as an IFN-γ-responsive gene 40 . In other cancers in which a florid antigen-driven immune response and concomitant adaptive immune suppression via PD-L1 exist within the tumor microenvironment, blockade of the PD-1 receptor is an effective therapeutic strategy 13,15 . In support of this, recent studies have shown that the efficacy of PD-1 blockade is inextricably linked with the existence of an interferon-driven immune response and expression of MHC class II 13,15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with recent observations that PD-L1 ( CD274 ) is a BCL6-supressed gene 41 , and a well-characterized role for PD-L1 as an IFN-γ-responsive gene 40 . In other cancers in which a florid antigen-driven immune response and concomitant adaptive immune suppression via PD-L1 exist within the tumor microenvironment, blockade of the PD-1 receptor is an effective therapeutic strategy 13,15 . In support of this, recent studies have shown that the efficacy of PD-1 blockade is inextricably linked with the existence of an interferon-driven immune response and expression of MHC class II 13,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In other cancers in which a florid antigen-driven immune response and concomitant adaptive immune suppression via PD-L1 exist within the tumor microenvironment, blockade of the PD-1 receptor is an effective therapeutic strategy 13,15 . In support of this, recent studies have shown that the efficacy of PD-1 blockade is inextricably linked with the existence of an interferon-driven immune response and expression of MHC class II 13,15 . Together, these observations suggest that the greatest potentiation of anti-tumor immunity in GCB-derived malignancies may be achieved through stimulation of interferon signaling and MHC class II expression by HDAC3 inhibition, in combination with the inhibition of adaptive immune suppression using PD-L1/PD-1 neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, angiogenesis signature can predict the clinical response to atezolizumab‐bevacizumab combination therapy in renal cell carcinoma . In melanoma, MHC protein expression can predict differential activity to anti‐CTLA4 or anti‐PD1 . Development of a universal biomarker platform for HNSCC treatment, including immunotherapy, is becoming increasingly essential for guiding personalized therapy.…”
Section: Anti‐pd1/pd‐l1 Therapy For Hnscc: Future Perspectivesmentioning
confidence: 99%
“…88 In melanoma, MHC protein expression can predict differential activity to anti-CTLA4 or anti-PD1. 89 Development of a universal biomarker platform for HNSCC treatment, including immunotherapy, is becoming increasingly essential for guiding personalized therapy. Human papillomavirus (HPV) associated oropharyngeal carcinoma is considered as a malignancy with better prognosis.…”
Section: Biomakers For Personalized Cancer Immunotherapymentioning
confidence: 99%